Synthesis and Characterization of Transition Metals Coordination Compounds Based on Bioactive Spatial Alicyclic Hydrazide-Hydrazones - Lekishvili, N.; Barbakadze, Kh. (Asian Journal of Chemistry, 2012)
New coordination compounds of transition metals based on bioactive adamantane-containing hydrazide-hydrazones have been synthesized. By using of the data of IR and NMR spectral, thermal (TGA, DTA) and elemental analysis and by molar conductivity the structure of the obtained compounds have been established. By using model systems and semi empirical quantumchemical AM1 method the electronic structure and complex forming capacity of obtained ligands have been established. It was shown that the organic ligand behaved as cyclic-bidentate (electron donor atoms -N and O) through the carbonyl oxygen and the NH2- or azomethine nitrogen atoms. The bactericide activity of the initial ligands and obtained coordination compounds towards test objects has been studied.